The Impact of Pets on Everyday Life for Older Adults During the COVID-19 Pandemic - Applebaum, Jennifer W.; Ellison, Carlyn; Struckmeyer, Linda; Zsembik, Barbara A.; McDonald, Shelby E. (Frontiers in Public Health, 2021)
Purpose: The social and behavioral health of older adults is of particular concern during the COVID-19 pandemic. It is estimated that at least 50% of older adults in the U.S. have pets; while pets may be a source of support, they could also pose unique challenges during an already trying time. We aimed to investigate how pets impacted the everyday lives of older adults in the early stages of the COVID-19 pandemic. Methods: A large survey of U.S. pet owners (n = 2,068) was administered to assess the impact of relationships with pets during COVID-19 on human health and well-being. We conducted bivariate analyses to compare levels of social support, loneliness, pet attachment, and family income for a subset of older adults (ages 65 and older) with a younger comparison group (ages 18–64). Using thematic and content analysis, we analyzed two open-ended prompts from age 65+ respondents (n = 122): (1) the pros and cons of living with pets during the pandemic, and (2) advice for those living with pets in future pandemics. Results: Older adults, on average, reported lower levels of social support and less loneliness than respondents below age 65. There were no significant differences in strength of attachment to pets nor income between the younger and older respondents. For the open-ended prompt regarding pros and cons, we coded three emerging themes and related sub-themes: (1) pros (company; more time together; life purpose or meaning; love; support; stress relief; routine; distraction; exercise), (2) cons (general worry; potential for illness; limited participation; veterinary care access; obtaining supplies; difficulty meeting pet needs; financial concerns), and (3) no difference. Advice shared was coded into 13 themes/sub-themes: pets' health and welfare; make plans; veterinary information; treat pets like family; don't abandon pets; human health and well-being; stay calm; enjoy pets; keep routine; be careful of transmission; seek community resources; keep supplies stocked; and finances. Conclusions: Pets may fulfill some social and emotional needs for older adults during this particularly isolating event; equally important to consider are the challenges that may be precipitated by and/or exacerbated by this public health emergency.